Study of student’s awareness towards the factors of air pollution: A case study of BAS students, UiTM Melaka City Campus / Nawal Mohd Zin and Siti Zulaikha Yahya - Mohd Zin, Nawal; Yahya, Siti Zulaikha (Faculty of Administrative Science and Policy Studies, 2012)
Pollution is one of the most serious problems facing the world today that is contamination of water, air, land and noise. Pollution has upset the balance of nature, destroyed many form of wild life and cause a variety of illness. It occurs on each but it is most well known in industrial countries. Some cases of air pollution are the most serious pollutions that are occur which gives bad impact towards people. the case of Indonesia forest burning that cause air pollution are most crucial cases that occur in every year and Sumatera’s close neighboring countries are Thailand, Malaysia and Singapore, while Kalimantan’s are Malaysia and Brunei Darussalam that are affect from the air pollution. Those are the countries that directly affected by the forest fires. As the dry season reaches its peak in Southeast Asian region, Indonesia is having its annual environmental problem that is the forest fires. Although the forest fires to some extent are part of traditional agriculture method, yet 81.1% of the forest burning is happening in industrial forest. (Jimmy Tanaya, 2007)